Effects of different agricultural organic wastes on soil GHG emissions: During a 4-year field measurement in the North China Plain. (November 2018) - Li, Zhejin; Wang, Dong; Sui, Peng; Long, Pan; Yan, Lingling; Wang, Xiaolong; Yan, Peng; Shen, Yawen; Dai, Hongcui; Yang, Xiaolei; Cui, Jixiao; Chen, Yuanquan
Highlights: GHG emissions induced by different organic wastes were evaluated. Different organic wastes returning to soil exhibited different results in the trials. Compared with CF treatment, organic wastes applied to soil significantly increased GHG emissions. Biogas residue returning emitted minimum GHG emissions among different types of organic wastes. Abstract: Large quantities and many varieties of agricultural organic wastes are produced in China annually. Applying agricultural organic wastes to soil plays an essential role in coping with the environmental pollution from agricultural wastes, solving the energy crisis and responding global climate change. But there is little information available on the effects of different agricultural organic wastes on soil greenhouse gas (GHG) emissions. The objectives of this study were to investigate and compare the impacts of different organic wastes on soil GHG emissions during a 4-year field experiments in the North China Plain, as well as analyze the influential factors that may be related to GHG emissions. The treatments were: crop straw (CS), biogas residue (BR), mushroom residue (MR), wine residue (WR) and pig manure (PM) returning to soil, as well as a control with no organic waste applied to soil but chemical fertilizer addition only (CF). The results showed that compared with CF treatment, organic material applied to soil significantly increased GHG emissions and emissions followed the order of WR(27, 961.51 kg CO2 -eq/ha/yr) > PM(26, 376.50 kg CO2 -eq/ha/yr) > MR(23, 366.60 kg CO2 -eq/ha/yr) > CS(22, 434.44 kg CO2 -eq/ha/yr) > BR (22, 029.04 kg CO2 -eq/ha/yr) > CF(17, 402.77 kg CO2 -eq/ha/yr), averagely. And considering the affecting factors, GHG emissions were significantly related to soil temperature and soil water content. Different organic wastes also affected soil total organic carbon (TOC), microbial carbon (MBC) and dissolved organic carbon (DOC) contents, which related to GHG emissions. Further analysis showed that characteristics of organic wastes affected GHG emissions, which included C-N ratio, lignin, polyphenol, cellulose and hemicellulose. Our study demonstrates that biogas residue returning to soil emitted minimum GHG emissions among these different types of organic wastes, which provided a better solution for applying organic wastes to mitigate soil GHG emissions.